Service Separation and Customer Satisfaction: Assessing the Service Separation/Customer Integration Paradox. (August 2013) - Paluch, Stefanie; Blut, Markus
Remote services are often provided without customer-provider contact for remote diagnostics, repair, and maintenance purposes in business-to-business industries such as information technology, medical health care, and mechanical engineering. Two empirical studies (Studies 1 and 2) suggest that numerous characteristics of remote services are critical to customer satisfaction: (1) security, (2) reliability, (3) level of process integration, (4) economic benefit, (5) post-provision documentation, (6) exchange options, (7) individualization, and (8) support services. Study 3 revealed a paradox that complicates service provision—a situation in which customers experience ambivalent feelings toward service separation as associated with remote services. They express (i) a strong desire to be part of the remote service provision in order to maintain control over the process, while at the same time, (ii) for personal and contractual reasons they do not want to be integrated into the process. Satisfaction levels were found to vary depending on how customers assess physical and mental service separation. We identified service initiation as a situational factor influencing the shift from a positive to a negative assessment of service separation. To prevent customer dissatisfaction, service providers should integrate customers into service provision for provider-initiated services, whereas for customer-initiated services they should not bring the customer in.